SOCIAL SECURITY MEASURES IN INFORMAL SECTOR IN KERALA - Deepa V. D. and D. Retnaraj
The informal sector is growing continuously in India and Kerala is no exception. However, majority of the informal sector workers are left without social security benefits. This paper argues that though several social security schemes are on paper, vulnerability of workers remain as before as small proportion of workers are covered.